Expanding the strategic and clinical leadership role of accredited specialists. (11th July 2022) - Parsons, V; Pattani, S; Gilbey, A; Madan, I; Harling, C; Muiry, R; de Bono, A
Abstract: Background: We sought to explore the value and benefits of accredited specialists employed in the National Health Service (NHS), and proposed strategies for expanding their role. Aims: To explore the core characteristics of accredited specialists and to examine how their skills could be further utilized to enhance occupational health (OH) services. Methods: Mixed methods comprising a survey and qualitative work. Results: OH survey was completed by 65 of 128 (51%) respondents. Nine accredited specialists and 16 stakeholders contributed qualitative data. Most OH departments were located in acute NHS trusts and additionally provided externally contracted services. We found a large variation in OH staffing and OH services delivered. The COVID pandemic created unprecedented challenges and required expansion in services to meet demand. The majority of respondents described greater recognition and appreciation by others of accredited specialists and OH teams for their specialist contribution during the pandemic. From the qualitative data, we identified two overarching themes. 'Professional credibility has currency' (Theme 1) and 'A visionary future' (Theme 2). A series of sub-themes are described. Conclusions: Accredited specialists employed in the NHS possess a core set of attributes and capabilities, and are skilful at delivering strong, influential and impactful clinical and strategic leadership across the NHS hierarchy and landscape. The COVID pandemic provided valuable opportunities for them to showcase their specialist clinical and leadership skills. The current wider reorientation of NHS clinical services offers bold new ways to expand their role beyond traditional clinical boundaries. Abstract : Results from a study exploring the development and use of core attributes (such as skills, experiences and professional relationships) and expertise of in-house accredited specialists in occupational medicine working in the National Health Service (NHS), and of the COVID-19-related work activities of their highly skilled OH workforce. The study makes a number of recommendations for expanding their strategic and clinical leadership role across the wider NHS landscape.